Psychometric Validation of the Chinese Version of the Lymphedema Functioning, Disability, and Health Questionnaire for Upper Limb Lymphedema in Patients With Breast Cancer–Related Lymphedema. Issue 1 (15th January 2022) - Zhao, Huihui; Wu, Yanni; Tao, Yanling; Zhou, Chunlan; De Vrieze, Tessa; Li, Xiaojin; Chen, Liling
Abstract : Background: Breast cancer–related lymphedema (BCRL) has a notable impact on patients' quality of life. However, no instrument is available to assess the problems in functioning due to BCRL in China. Objective: The aims of this study were to translate and validate a Chinese version of the Lymphedema Functioning, Disability, and Health Questionnaire for Upper Limb Lymphedema (Lymph-ICF-UL). Methods: A process of translation and cultural adaptation was conducted based on international standards. The study included 155 patients with BCRL and 90 patients without lymphedema. Psychometric properties that were tested consisted of internal consistency, test-rest reliability, content, construct and discriminant validity. Results: The Cronbach's α was .92, and intraclass correlation coefficient was 0.83. Content validity was confirmed by a sufficient content validity index in item level and scale level. Exploratory factor analysis identified 5 factors accounting for 62.44% of the total variance, and confirmatory factor analysis fit indices were acceptable. Convergent validity was supported by a moderate correlation with the 36-item Short-Form Health Survey Questionnaire and relatively weak correlations with the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire Core 30. There was good divergent validity with all hypotheses evaluating divergent validity were confirmed. Significant differences were found between the lymphedema and nonlymphedema groups. Conclusion: The Chinese version of the Lymph-ICF-UL is a valid and reliable instrument that can be used in both clinical and scientific settings in China. Implications: The Chinese version of the Lymph-ICF-UL could be applicable in assessing the impairments in function, activity limitations, and participation restrictions of Chinese patients with BCRL.